2012
DOI: 10.3233/wor-2012-0410-1933
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and organizational risk and prevalence of low back pain in the old adults caregivers of a nursing home in Joao Pessoa/PB

Abstract: The objective present study was to investigate the presence of low back pain in caregivers of a nursing home, related with the labored activities executed by these workers. 16 subjects were investigated, 15 female and one male, with 40,8 age average all being caregivers as their profession. It consisted of three phases, where the first concerns the analysis of the collective work, assessed in a perspective of caregivers, Second, a postural assessment to verify the retractions in such workers and the third stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Consequently, care workers often complain of back pain [11,12]. Several of the studies that have examined musculoskeletal injuries, found that a positive work environment, including social support at work [13], good relationship with colleagues [14], and the availability of ergonomic equipment and training programs, was associated with a decrease in the rate of compensation claims for injuries [15][16][17]. However, most of these findings are not generalizable to all nursing home care workers, as they were limited to nurse aides [18].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, care workers often complain of back pain [11,12]. Several of the studies that have examined musculoskeletal injuries, found that a positive work environment, including social support at work [13], good relationship with colleagues [14], and the availability of ergonomic equipment and training programs, was associated with a decrease in the rate of compensation claims for injuries [15][16][17]. However, most of these findings are not generalizable to all nursing home care workers, as they were limited to nurse aides [18].…”
Section: Introductionmentioning
confidence: 99%
“…Work-related causes of LBP can be physical, including physical fatigue from work activities or the posture in which the work is performed. In addition, LBP can be psychological, related to work stress, as is often seen in nursing and caregiving (Fujimura et al 1995, Karahan et al 2009, Ribeiro et al 2012, Yeung 2012. With the ageing of developed societies, the number of caregivers caring for elderly people at home is growing (Jang et al 2012, Hiel et al 2015, de Meijer et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…, Ribeiro et al . , Yeung ). With the ageing of developed societies, the number of caregivers caring for elderly people at home is growing (Jang et al .…”
Section: Introductionmentioning
confidence: 99%